(untitled) (Journal of Agriculture and Plant Sciences, 2025)
This study is a field experiment of using clove tea as an effective treatment against varroa mites (Varroa destructor), by spraying the tea directly on all the frames in the beehive. Two experiments were conducted, one for 14 weeks, with an application of clove tea once every 2 weeks and the other for 8 weeks with an application once per week. In both experiments after 6 applications, the tea-treated varroa-infected beehives were completely varroa-free, concluding complete eradication.